Comparison of Apgar Score of Newborns After Cesarean Section by Induction of General Anesthesia and Spinal Anesthesia - Mina Alipoor; Bahar Noori; Zahra Asadollahi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Cesarean section surgery has grown globally in the past decade, using general and intraspinal anesthesia methods, which significantly influence newborn Apgar scores. Therefore, this study was conducted with the aim of comparing the Apgar scores of newborns after cesarean section by induction of general anesthesia or spinal anesthesia in Rafsanjan city from 2018 to 2019. Materials & Methods: This study is a double-blind randomized clinical trial that was conducted on 69 pregnant mothers through available sampling. Participants were divided into two groups, the first group (n=34) was induced under general anesthesia with 1-2 mg/kg of Ketamine along with 2 mg/kg of Propofol. The second group (n=35) underwent spinal anesthesia with 5 mg Bupivacaine 5%. In order to compare the Apgar score of newborns in two methods of general anesthesia and intraspinal anesthesia, in minutes 1, 5, 10, and 15, a two-way repeated measures ANOVA and Bonferroni's test were used. Data analyzed by SPSS V.21 at the significance level of 0.05. Results: Using the repeated measures ANOVA, found that the average Apgar score of the babies in the two groups that underwent general anesthesia and spinal anesthesia did not have a significant difference (P=0.213). However, the increase in Apgar scores over time was statistically significant (P < 0.001), meaning that in both groups, regardless of the anesthesia method, over time, the Apgar score increased. Conclusion: There is no significant relationship between the choice of anesthesia method and the Apgar score of newborns in women candidates for caesarean section.